Model Formulation for Quantitative Research on Purchase Intentions of Car Owners - Balakrishnan Menon (International Journal of Research in Social Sciences, 2011)
Automobile Industry in India is influenced by the presence of national and multi-national manufacturers. The presence of many manufacturers and brands in the state provides many choices to the customer. These manufacturers offer similar value proposition, making the passenger car segment being highly commoditized. Customers no longer consider engine performance, as a major factor, as it is expected to be a standard already in place. They look for those differentiating parameters, which can make the choice from one brand to another. The main purpose of this paper is to come up with the identification of possible parameters that influence the consumer purchase behaviour patterns of passenger car owners in the State of Kerala. It is also aimed to develop a theoretical model, which influence the consumer purchase patterns of passenger cars, so that further research could be done, based on the model and the identified parameters.